Economic Freedom and Foreign Direct Investment: How different are the MENA countries from the EU? - Caetano, José Martins (2013)
The risk perceived by investors is crucial in the decision to invest, in particular when it concerns a foreign country. The investment risk associated is a multi-faceted element given that it reflects many aspects that are relevant to (foreign) investors, such as the level of transparency, corruption, rule of law, governance, etc. In this paper we consider the level of economic freedom, as provided by the “Heritage Foundation”, for the most recent years, in order to analyse how is this measure of risk related to the inward foreign direct investment performance index, as provided by the UNCTAD. Given the subjectivity of risk an appropriate methodology consists on using fuzzy logic clustering, which is applied in the paper in order to verify how different the MENA region is from the set of EU-member states. The results show that economic freedom and inward FDI are positively associated, in particular in the cluster of countries that present a higher economic freedom. Of particular interest is the result that some MENA countries belong to the same cluster of most of the EU-countries.